Fabrication and characterization of metal oxide thin films by sputtering method for PN junction applications - Azmizam Manie @ Mani (2017)
Metal oxides are the most common minerals on the earth due to their compositions, chemical and physical properties and widely used in many fields such as transparent electronics, piezoelectric transducers, sensors and electro-optical devices. Cu2O and ZnO one of the well-known metal oxide material among the researcher and both materials receive positive review from lots of researchers. ZnO is a natural n-type semiconductor and-Cu2O is a p-type semiconductor. Therefore, this research describes about the fabrication of Cu2O and ZnO thin films and discusses the characteristic of thin films deposited by RF magnetron sputtering technique. The substrate used to deposit thin films will be- cut, cleaned and heated. Favorable deposition parameter such as nominal thickness from 100 nm to SOO nm and substrate temperature from SO °C to 250 °C is chosen in order to analyze the characteristic of thin films. ZnO thin films show preferentiaJ orientation of (0 ·o 2) at 34° am;i the crystallite grain size increase as the increment of thin films thickness. ZnO thin films also shows same preferential orientation of (0 0 2) at 34° and the crystallite grain size also increase as the increment of thin films substrate temperature. The ZnO estimated optical band gap was 3.20- 3.24 eV for different thin film thickness while 3.26 eV for different thin film substrate temperature. The surface roughness of ZnO thin films was found increased as the thickness increased, while the surface roughness was found decreased as the substrate temperature increased. Cu2O thin films show major preferential orientation of (1 1 1) at 36° and minor preferential orientation of (1 1 O) and (1 1 3) at 31 ° and 64°, the crystallite grain size increase as the increment of thin films thickness. Cu2O thin films also shows same preferential orientation of (1 1 1) at 36° and the crystallite grain size also increase as the increment of thin films substrate temperature. The Cu2O estimated optical band gap was in range of 1.95 -2.05 eV for different thin film thickness while for different substrate temperature was about 2.0 - 2.1 eV. The surface roughness results of Cu2O thin films was found increased as the thickness increased, while the surface roughness was found decreased as the substrate temperature increased. The closest ideality factor obtain for Cu2O/ZnO to the ideal ideality factor was 12.5, found to be at thickness Cu2O of 200nm paired with the ZnO at thickness of 500nm.